The effect of Zostera noltei recolonization on the sediment mercury vertical profiles of a recovering coastal lagoon - Oliveira, V.H.; Fonte, B.A.; Costa, F.; Sousa, A.I.; Henriques, B.; Pereira, E.; Dolbeth, M.; Díez, S.; Coelho, J.P. (Chemosphere (Oxford), 2023)
Mercury's extreme toxicity and persistence in the environment justifies a thorough evaluation of its dynamics in ecosystems. Aveiro Lagoon (Portugal) was for decades subject to mercury effluent discharges. A Nature-based Solution (NbS) involving Zostera noltei re-colonization is being tested as an active ecosystem restoration measure. To study the effect of Zostera noltei on the sediment contaminant biogeochemistry, seasonal (summer/winter) sediment, interstitial water and labile mercury vertical profiles were made in vegetated (Transplanted and Natural seagrass meadows) and non-vegetated sites (Bare-bottom area). While no significant differences (p > 0.05) were observed in the sedimentary phase, Zostera noltei presence reduced the reactive/labile mercury concentrations in the top sediment layers by up to 40% when compared to non-vegetated sediment, regardless of season. No differences were found between vegetated meadows, highlighting the fast recovery of the contaminant regulation ecosystem function provided by the plants after re-colonization and its potential for the rehabilitation of historically contaminated ecosystems.Mercury's extreme toxicity and persistence in the environment justifies a thorough evaluation of its dynamics in ecosystems. Aveiro Lagoon (Portugal) was for decades subject to mercury effluent discharges. A Nature-based Solution (NbS) involving Zostera noltei re-colonization is being tested as an active ecosystem restoration measure. To study the effect of Zostera noltei on the sediment contaminant biogeochemistry, seasonal (summer/winter) sediment, interstitial water and labile mercury vertical profiles were made in vegetated (Transplanted and Natural seagrass meadows) and non-vegetated sites (Bare-bottom area). While no significant differences (p > 0.05) were observed in the sedimentary phase, Zostera noltei presence reduced the reactive/labile mercury concentrations in the top sediment layers by up to 40% when compared to non-vegetated sediment, regardless of season. No differences were found between vegetated meadows, highlighting the fast recovery of the contaminant regulation ecosystem function provided by the plants after re-colonization and its potential for the rehabilitation of historically contaminated ecosystems.